Demand Storage, Market Liquidity, and Price Volatility - Daniels, MG; Farmer, J; Iori, G; Smith, E (2013)
The limit order book is a device for storing demand and effecting trades that is the primary mechanism for price formation in most modern financial markets. We study the limit order book under a random process model of order flow, using simulations and an analytic treatment based on a master equation. We make testable predictions of the price diffusion rate, the depth of stored demand vs. price, the bid-ask spread, and the price impact. Our model provides an explanation for the empirically observed concave form of the price impact function.